Collaborative Online International Learning (COIL) between Spanish and Ukrainian Students: New Tasks and New Relationships - Inmaculada Fortanet-Gómez; Viktoriia Drobotun (Miscelánea: A Journal of English and American Studies)
Nowadays, our professional lives face challenges that inevitably require a quick reaction and a shift in the field of education. Moreover, globalisation and the ongoing war in Ukraine motivate teachers to look for new opportunities to communicate across cultures. This research aims to analyse students’ perceptions of the effects of collaborative online international learning (COIL). The study participants were 12 fourth-year Ukrainian students from Taras Shevchenko National University of Kyiv who were taking the course on Academic English within the Languages, Literature and Translation program and a group of 20 Spanish fifth-year students from Universitat Jaume I who were enrolled in the Business English course as part of the dual degree in Business Administration and Law. The methodology consisted of three stages. Firstly, participants used online communication tools to establish contacts with partners. Secondly, students discussed the topic of corporate sustainability on Zoom. Thirdly, each group used online collaborative teaching (OCT) to write an opinion essay. Results from the final questionnaire after the COIL experience confirmed that, despite the difficulties due to the ongoing war in Ukraine, students’ perceptions of their experience of COIL were positive. They were more motivated and believed the activity had helped them to improve their writing and speaking skills as well as their intercultural competence.